Parents as partners in education : families and schools working together - Berger, Eugenia Hepworth (Upper Saddle River, N.J. : Merrill, 2000)
This book includes a comprehensive look at parent-school partnerships, and it also updates the national emphasis on home-school participation.
Keywords: Education; Teachers; Home and school -- United States; Education -- Parent participation -- United States